Robotics Inspired Renewable Energy Developments: Prospective Opportunities and Challenges - Jamshed Iqbal; Ali Al-Zahrani; Soltan Abed Alharbi; Anas Hashmi (IEEE Access, 2019)
The domain of Robotics is a good partner of renewable energy and is becoming critical to the sustainability and survival of the energy industry. The multi-disciplinary nature of robots offers precision, repeatability, reliability, productivity and intelligence, thus rendering their services in diversified tasks ranging from manufacturing, assembling, and installation to inspection and maintenance of renewable resources. This paper explores applications of real robots in four feasible renewable energy domains; solar, wind, hydro, and biological setups. In each case, existing state-of-the-art innovative robotic systems are investigated that have the potential to create a difference in the corresponding renewable sector in terms of reduced set-up time, lesser cost, improved quality, enhanced productivity and exceptional competitiveness in the global market. Instrumental opportunities and challenges of robot deployment in the renewable sector are also discussed with a brief case study of Saudi Arabia. It is expected that the wider dissemination of the instrumental role of robotics in renewable energy will contribute to further developments and stimulate more collaborations and partnerships between professionals of robotics and energy communities.